The need for local governance of global commons: The example of blue carbon ecosystems - Christine Merk; Jonas Grunau; Marie-Catherine Riekhof; Wilfried Rickels (Kiel Institute for the World Economy (IfW), 2022)
To limit global warming to 1.5°C, vast amounts of CO2 will have to be removed from the atmosphere via Carbon Dioxide Removal (CDR). Enhancing the CO2 sequestration of ecosystems will require not just one approach but a portfolio of CDR options, including so-called nature-based approaches alongside CDR options that are perceived as more technical. Creating a CDR "supply curve" would however imply that all carbon removals are considered to be perfect substitutes. The various co-benefits of nature-based CDR approaches militate against this. We discuss this aspect of nature-based solutions in connection with the enhancement of blue carbon ecosystems (BCE) such as mangrove or seagrass habitats. Enhancing BCEs can indeed contribute to CO2 sequestration, but the value of their carbon storage is low compared to the overall contribution of their ecosystem services to wealth. Furthermore, their property rights are often unclear, i.e. not comprehensively defined or not enforced. Hence, payment schemes that only compensate BCE carbon sequestration could create tradeoffs at the expense of other important, often local, ecosystem services and might not result in socially optimal outcomes. Accordingly, one chance for preserving and restoring BCEs lies in the consideration of all services in potential compensation schemes for local communities. Also, local contexts, management structures, and benefit-sharing rules are crucial factors to be considered when setting up international payment schemes to support the use of BCEs and other nature- or ecosystem-based CDR. However, regarding these options as the only hope of achieving more CDR will very probably not bring about the desired outcome, either for climate mitigation or for ecosystem preservation. Unhalted degradation, in turn, will make matters worse due to the large amounts of stored carbon that would be released. Hence, countries committed to climate mitigation in line with the Paris targets should not hide behind vague pledges to enhance natural sinks for removing atmospheric CO2 but commit to scaling up engineered CDR.
Keywords: Q54; Q57; Q58; 330; Carbon Dioxide Removal; nature-based solutions; blue carbon ecosystems; common pool resources; governance; property rights